#TITLE_ALTERNATIVE# - HARTANTO (NIM: 25112018) ; (Pembimbing: Dr. Ir. Kosasih Prijatna, M.Sc ; Sella Lestari Nurm, PRAYUDHA
Sea level change rate in the Western Pacific Ocean is one of the biggest in the world. There are 2 factors affecting this phenomenon, the steric effect and the eustatic effect. In the 1992-2012 period, the total sea level change rate in this region was 6,982 ± 3,493 mm/year. Based on temperature and salinity profiles from Argo floats, the steric sea lavel change rate in the 2000-2013 period is 14,352 ± 13,002 mm/year. This result referred to 900 dBar reference pressure. We do the linear regression to the GRACE monthly data to generate the eustatic sea level change rate. The result is 0,194 ± 0,092 mm/year in the 2004-2012 period. We conclude that the correlation between ocean mass and Sea Level Anomaly (SLA) is more significant than the correlation between steric sea level height and SLA. However, such a more advance investigation is needed to determine which factor contributes more in this regional sea level variation